NLRP10 Enhances CD4+ T-Cell-Mediated IFNγ Response via Regulation of Dendritic Cell-Derived IL-12 Release - Vacca, Maurizio; Böhme, Julia; Zambetti, Lia Paola; Khameneh, Hanif Javanmard; Paleja, Bhairav S.; Laudisi, Federica; Ho, Adrian W. S.; Neo, Kurt; Leong, Keith Weng Kit; Marzuki, Mardiana; Lee, Bernett; Poidinger, Michael; et al. (Frontiers in Immunology, 2017)
NLRP10 is a NOD-like receptor that functions as an intracellular pattern-recognition receptor for microbial and non-microbial products. Here, we generated a Nlrp10-/- mouse to delineate the role of NLRP10 in the host immune response and found that Nlrp10-/- dendritic cells (DCs) elicited sub-optimal IFNg production by antigen-specific CD4+ T cells compared to wild-type (WT) DCs. In response to T-cell encounter, CD40 ligation or Toll-like receptor (TLR) 9 stimulation, Nlrp10-/- DCs produced low levels of IL-12, due to a substantial decrease in NF-kB activation. Defective IL-12 production was also evident in vivo and affected IFNg production by CD4+ T cells. Upon Mycobacterium tuberculosis infection, Nlrp10-/- mice displayed diminished T helper 1-cell responses and increased bacterial growth compared to WT mice. These data indicate that NLRP10-mediated IL-12 production by DCs is critical for IFNg induction in T cells and contributes to promote the host defense against Mycobacterium tuberculosis.